Mold modification methods to fix warpage problems for plastic molding products. Issue 1 (2nd January 2016) - Fu, Junyu; Ma, Yongsheng
ABSTRACT: Warpage is a common quality problem for plastic molding products and it is influenced by numerous factors. Molding simulation software packages are widely used to analyze the molding conditions. However, the current practice typically addresses the warpage problem at the mold design stage. When the mold has already been manufactured, solving the warpage problem becomes difficult. In this paper, we proposed a simulation workflow aiming to analyze the reasons that cause warpage after pilot molding, and further, four possible methods to resolve such problems. Two case studies are presented to show the available solution options. For those given examples, by using mold inserts of different material and adding more cooling channels respectively, the warpages of the products were solved. GRAPHICAL ABSTRACT: